Acrylic resin, preparation method and application thereof, and acrylic powder coating

By using the second crosslinking monomer and the epoxy first crosslinking monomer in the acrylic resin, the crosslinking degree and thermal stability of the resin are improved, the problem of insufficient thermal stability of the existing resin is solved, and higher weather resistance and mechanical properties are achieved.

CN119823312AActive Publication Date: 2025-04-15NEWMAT (BEIJING) ENVIRONMENTAL MATERIALS TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411958552.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing acrylic resins have shortcomings in thermal stability and are difficult to meet the high-temperature performance requirements of photovoltaic module packaging materials.

Method used

A second crosslinking monomer containing at least two unsaturated bonds and containing end-group carbon carbon double bonds is used to combine with the epoxy type first crosslinking monomer to improve the crosslinking degree and thermal stability of the acrylic resin.

Benefits of technology

It significantly improves the thermal stability of the acrylic resin, enhances its weather resistance and mechanical properties, while maintaining good light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216506840000091
    Figure BDA0005216506840000091
Patent Text Reader

Abstract

The invention provides acrylic resin, a preparation method and application thereof and an acrylic powder coating, and belongs to the technical field of photovoltaic packaging materials. The acrylic resin is prepared from the following raw materials in parts by mass: 10-60 parts of a soft monomer, 30-70 parts of a hard monomer, 20-50 parts of a first cross-linking monomer, 0.2-0.5 part of a second cross-linking monomer, 1-5 parts of an initiator and 60-300 parts of a solvent, the first crosslinking monomer contains an epoxy group; the second crosslinking monomer contains at least two unsaturated bonds, and the at least two unsaturated bonds comprise end group carbon-carbon double bonds; the soft monomer is an alkyl acrylate compound. The second cross-linking monomer is used, the second cross-linking monomer is limited to contain end group carbon-carbon double bonds, the second cross-linking monomer can realize carbon-carbon double bond self-crosslinking, the crosslinking degree is improved, and the thermal stability of the acrylic resin is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic packaging materials, and in particular to an acrylic resin and a preparation method and application thereof, and an acrylic powder coating. Background Art

[0002] Photovoltaic power generation is a technology that uses the photovoltaic effect of semiconductor interfaces to directly convert light energy into electrical energy. It mainly consists of three parts: solar panels (modules), controllers and inverters. Traditional photovoltaic modules are encapsulated with glass, which is heavy, more than 10kg per square meter, which makes installation and construction difficult. Therefore, researchers are looking for new encapsulation materials to replace glass to reduce weight and meet the technical standards of the photovoltaic industry, such as UV resistance, aging resistance, impact resistance and fire resistance.

[0003] Related art discloses using acrylic powder coating as a new type of packaging material with light weight, high transparency and strong weather resistance, such as preparing epoxy acrylic powder coating resin with cross-linking monomers containing epoxy monomers and / or hydroxyl monomers, so that the obtained acrylic resin has excellent light transmittance, flexibility and good impact resistance; high light transmittance acrylic resin prepared with methacrylic acid, methyl methacrylate, n-butyl methacrylate, glycidyl methacrylate, functional monomers (including one or more of hexafluorobutyl methacrylate, n-dodecyl acrylate and polyethylene glycol methacrylate) and styrene has good mechanical strength. However, the acrylic resin in the related art still has the problem of poor thermal stability. Summary of the invention

[0004] In view of this, the object of the present invention is to provide an acrylic resin and its preparation method and application, and acrylic powder coating. The acrylic resin provided by the present invention uses a second crosslinking monomer containing at least two unsaturated bonds and a terminal carbon-carbon double bond to improve the thermal stability of the acrylic resin.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides an acrylic resin, which is prepared from the following raw materials in parts by weight:

[0007] 10-60 parts of soft monomer, 30-70 parts of hard monomer, 20-50 parts of first crosslinking monomer, 0.2-0.5 parts of second crosslinking monomer, 1-5 parts of initiator and 60-300 parts of solvent;

[0008] The first crosslinking monomer contains an epoxy group; the second crosslinking monomer contains at least two unsaturated bonds, and the at least two unsaturated bonds include a terminal carbon-carbon double bond;

[0009] The soft monomer is an alkyl acrylate compound.

[0010] Preferably, the second crosslinking monomer comprises allyl methacrylate and / or allyl acrylate.

[0011] Preferably, the mass fraction of the second cross-linking monomer in the raw material is 0.3 to 0.4 parts.

[0012] Preferably, the first cross-linking monomer includes one or more of glycidyl methacrylate, glycidyl acrylate, 4-hydroxybutyl acrylate glycidyl ether and versatile glycidyl carbonate.

[0013] The present invention also provides a method for preparing the acrylic resin described in the above technical solution, comprising the following steps:

[0014] Mixing the soft monomer, the hard monomer, the first crosslinking monomer, the second crosslinking monomer and the initiator to obtain a mixed solution;

[0015] The mixed solution is added dropwise into a solvent to carry out a polymerization reaction, thereby obtaining the acrylic resin.

[0016] Preferably, the dripping time is 3 to 6 hours.

[0017] Preferably, the temperature of the solvent is 130-150°C.

[0018] Preferably, the polymerization reaction temperature is 130-150° C., and the insulation time is 1-4 hours, wherein the insulation time is calculated from the completion of the dropwise addition.

[0019] The present invention also provides the use of the acrylic resin described in the above technical solution or the acrylic resin prepared by the preparation method described in the above technical solution as a photovoltaic module packaging material.

[0020] The present invention also provides an acrylic powder coating, comprising the following components in parts by mass: 100-140 parts of a resin, 12-40 parts of a curing agent and 0.2-2 parts of an accelerator, wherein the resin is the acrylic resin described in the above technical solution or the acrylic resin prepared by the preparation method described in the above technical solution.

[0021] The invention provides an acrylic resin, which is prepared from the following raw materials in parts by mass: 10 to 60 parts of a soft monomer, 30 to 70 parts of a hard monomer, 20 to 50 parts of a first crosslinking monomer, 0.2 to 0.5 parts of a second crosslinking monomer, 1 to 5 parts of an initiator and 60 to 300 parts of a solvent; the first crosslinking monomer contains an epoxy group; the second crosslinking monomer contains at least two unsaturated bonds, and the at least two unsaturated bonds include a terminal carbon-carbon double bond; the soft monomer is an alkyl acrylate compound.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention uses a second crosslinking monomer, and it is limited that the second crosslinking monomer contains at least two unsaturated bonds, and the at least two unsaturated bonds include terminal carbon-carbon double bonds. The second crosslinking monomer can achieve self-crosslinking of carbon-carbon double bonds, improve the crosslinking degree, and make the epoxy value 0.24-0.3 mol / 100g, thereby improving the thermal stability of acrylic resin; at the same time, by limiting the amount of each raw material, the acrylic resin improves weather resistance and thermal stability while maintaining light transmittance. At the same time, the raw materials used in the present invention are all common raw materials, and the cost is low.

[0024] The present invention also provides a method for preparing the acrylic resin described in the above technical solution, which has a simple polymerization process, low requirements on production equipment, and saves equipment costs.

[0025] Furthermore, the present invention controls the time of dripping and the holding time of the polymerization reaction, so that the number average molecular weight of the prepared acrylic resin is 2000-4000 and the molecular weight distribution is 1.6-1.8, thereby ensuring the thermal stability of the acrylic resin.

[0026] Furthermore, the present invention also limits the temperature of the solvent to 130-150° C., which can control the reflux state of the solvent, thereby controlling the reaction heat, making the polymerization reaction temperature stable, and further ensuring the stability of the resin performance. DETAILED DESCRIPTION

[0027] The present invention provides an acrylic resin, which is prepared from the following raw materials in parts by weight:

[0028] 10-60 parts of soft monomer, 30-70 parts of hard monomer, 20-50 parts of first crosslinking monomer, 0.2-0.5 parts of second crosslinking monomer, 1-5 parts of initiator and 60-300 parts of solvent;

[0029] The first crosslinking monomer contains an epoxy group; the second crosslinking monomer contains at least two unsaturated bonds, and the at least two unsaturated bonds include a terminal carbon-carbon double bond;

[0030] The soft monomer is an alkyl acrylate compound.

[0031] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.

[0032] In the present invention, the mass fraction of the soft monomer in the raw material is preferably 15 to 55 parts, specifically 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60 parts, and the soft monomer is an alkyl acrylate compound, and the function of the soft monomer is to provide resin toughness and corresponding adhesion.

[0033] In the present invention, the alkyl acrylate compound preferably includes one or more of methyl acrylate, ethyl acrylate, propyl acrylate and butyl acrylate (BA).

[0034] Based on the mass fraction of the soft monomer, the mass fraction of the hard monomer in the raw material is preferably 35 to 65 parts, specifically 30, 35, 40, 45, 50, 55, 60, 65 or 70 parts. The function of the hard monomer is to provide a certain hardness.

[0035] In the present invention, the hard monomer preferably includes one or more of methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobornyl methacrylate, dicyclopentadiene acrylate, dicyclopentadiene ethoxy acrylate, styrene, methyl styrene and acrylonitrile.

[0036] In the present invention, the mass fraction of the first cross-linking monomer in the raw material is preferably 25 to 45 parts, specifically 20, 25, 30, 35, 40, 45 or 50 parts.

[0037] Based on the mass fraction of the soft monomer, the first cross-linking monomer preferably includes one or more of glycidyl methacrylate, glycidyl acrylate, 4-hydroxybutyl acrylate glycidyl ether and versatile glycidyl carbonate.

[0038] Based on the mass fraction of the soft monomer, the mass fraction of the second cross-linking monomer in the raw material is preferably 0.3-0.4 parts, specifically 0.2, 0.3, 0.4 or 0.5 parts. The terminal carbon-carbon double bonds contained in the second cross-linking monomer can achieve self-cross-linking of the carbon-carbon double bonds, thereby improving the degree of cross-linking and further improving the thermal stability of the acrylic resin.

[0039] In the present invention, the second crosslinking monomer preferably includes allyl methacrylate and / or allyl acrylate.

[0040] Based on the mass fraction of the soft monomer, the mass fraction of the initiator in the raw material is preferably 2 to 4 parts, specifically 1, 2, 3, 4 or 5 parts.

[0041] In the present invention, the initiator is preferably an azo initiator and / or a peroxide initiator; the azo initiator preferably includes azobisisobutyronitrile and / or azobisisoheptanenitrile; the peroxide initiator preferably includes one or more of benzoyl peroxide, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, diisopropylbenzene hydroperoxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, di-tert-amyl peroxide, tert-butyl peroxy-2-ethylhexanoate and diisopropylbenzene peroxide.

[0042] Based on the mass fraction of the soft monomer, the mass fraction of the solvent in the raw material is preferably 80 to 250 parts, specifically 60, 80, 100, 120, 150, 200, 250 or 300 parts.

[0043] In the present invention, the solvent preferably includes one or more of toluene, xylene, trimethylbenzene, ethyl acetate, butyl acetate, tetrahydrofuran, ethylene glycol methyl ether and acetone.

[0044] In the present invention, the mass ratio of the soft monomer, the hard monomer, the first crosslinking monomer and the second crosslinking monomer is preferably 10:40:40:0.4. Under this raw material ratio, the acrylic resin has the best performance, weather resistance and thermal stability.

[0045] In the present invention, the mass ratio of the solvent to the monomer is preferably 1:1, and the monomer includes a soft monomer, a hard monomer, a first crosslinking monomer and a second crosslinking monomer. The effect of controlling the ratio is to obtain an acrylic resin with a suitable Tg and a suitable crosslinking degree.

[0046] In the present invention, the epoxy value of the acrylic resin is preferably 0.24 to 0.3 mol / 100 g, the light transmittance is preferably 92 to 94%, the number average molecular weight is preferably 2000 to 4000, and the molecular weight distribution is preferably 1.6 to 1.8.

[0047] The present invention also provides a method for preparing the acrylic resin described in the above technical solution, comprising the following steps:

[0048] Mixing the soft monomer, the hard monomer, the first crosslinking monomer, the second crosslinking monomer and the initiator to obtain a mixed solution;

[0049] The mixed solution is added dropwise into a solvent to carry out a polymerization reaction, thereby obtaining the acrylic resin.

[0050] The present invention mixes the soft monomer, the hard monomer, the first crosslinking monomer, the second crosslinking monomer and the initiator to obtain a mixed solution. The present invention has no special method for the specific manner of the mixing, and a method familiar to those skilled in the art can be used.

[0051] After obtaining the mixed solution, the present invention drops the mixed solution into a solvent to carry out a polymerization reaction to obtain the acrylic resin.

[0052] In the present invention, the dropping time is preferably 3 to 6 hours, specifically 3, 4, 5 or 6 hours. By controlling the dropping time, the present invention can make the number average molecular weight of the prepared acrylic resin 2000 to 4000 and the molecular weight distribution 1.6 to 1.8, thereby ensuring the thermal stability of the acrylic resin. If the dropping time is too long, the molecular weight distribution will become wider. If the dropping time is too short, the reaction will be incomplete.

[0053] In the present invention, the mixed solution is preferably added dropwise at a uniform speed.

[0054] In the present invention, the temperature of the solvent is preferably 130-150°C, specifically 130, 138, 140 or 150°C, which can control the reflux state of the solvent, thereby controlling the reaction heat, stabilizing the polymerization reaction temperature, and further ensuring stable resin performance.

[0055] In the present invention, the temperature of the solvent is preferably reached by programmed temperature increase, which can ensure the normal reflux state of the solvent and is conducive to controlling the heat change during the reaction, thereby achieving temperature stability.

[0056] In the present invention, the heating rate of the programmed temperature increase is preferably 20° C. every 15 minutes.

[0057] In the present invention, the polymerization reaction temperature is preferably 130-150°C, specifically 130, 138, 140 or 150°C, more preferably the polymerization reaction is carried out at a temperature at which the solvent refluxes, the insulation time is preferably 1-4h, specifically 1, 2, 3 or 4h, and the insulation time is calculated from the completion of the dropwise addition.

[0058] In the present invention, the polymerization reaction is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably nitrogen.

[0059] After the polymerization reaction is completed, the present invention preferably performs reduced pressure distillation on the obtained polymerization product to obtain the acrylic resin.

[0060] In the present invention, the vacuum degree of the reduced pressure distillation is preferably 0.098 MPa, and the temperature is preferably 100° C. The present invention has no special limitation on the time of the reduced pressure distillation, and the distillation is continued until no fraction is distilled out.

[0061] The present invention also provides the use of the acrylic resin described in the above technical solution or the acrylic resin prepared by the preparation method described in the above technical solution as a photovoltaic module packaging material.

[0062] The present invention also provides an acrylic powder coating, comprising the following components in parts by mass: 100-140 parts of a resin, 12-40 parts of a curing agent and 0.2-2 parts of an accelerator, wherein the resin is the acrylic resin described in the above technical solution or the acrylic resin prepared by the preparation method described in the above technical solution.

[0063] The mass fraction of the resin in the acrylic powder coating provided by the present invention can specifically be 100, 120 or 140 parts.

[0064] The mass fraction of the curing agent in the acrylic powder coating provided by the present invention is preferably 15 to 35 parts, specifically 12, 15, 20, 25, 30, 35 or 40 parts.

[0065] In the present invention, the curing agent preferably includes one or more of undecanedioic acid, dodecanedioic acid, tridecanedioic acid and tetradecanedioic acid.

[0066] The weight percentage of the accelerator in the acrylic powder coating provided by the present invention is preferably 0.5 to 15 parts, specifically 0.2, 0.5, 1, 1.5 or 2 parts.

[0067] In the present invention, the accelerator preferably includes one or more of 2-methylimidazole, zinc acetylacetonate, 2-mercaptobenzothiazole zinc salt (zinc salt MZ), hexadecyltrimethylammonium bromide and benzyltriethylammonium chloride.

[0068] The present invention also provides a method for preparing the acrylic powder coating described in the above technical solution, comprising the following steps: mixing a resin, a curing agent and an accelerator to obtain the acrylic powder coating.

[0069] In the present invention, the mixing temperature is preferably 80-120° C., specifically 80, 100 or 120° C. The present invention has no particular limitation on the mixing time, as long as the raw materials can be mixed uniformly.

[0070] In the present invention, the mixing preferably further comprises pulverizing and grinding in sequence to obtain the acrylic powder coating.

[0071] The present invention has no particular limitation on the specific parameters of the crushing and grinding, as long as the acrylic powder coating can pass through a 120-mesh sieve.

[0072] The present invention also provides an application of the acrylic powder coating of the above technical solution, preferably comprising the following steps: spraying the acrylic powder coating onto the surface of a substrate and then curing it, wherein the spraying is electrostatic spraying.

[0073] In the present invention, the substrate preferably includes an aluminum plate.

[0074] In the present invention, the aluminum plate is preferably surface treated, and the surface treatment is preferably to wipe dust and impurities on the surface of the aluminum plate with ethanol.

[0075] In the present invention, the parameters of the electrostatic spraying preferably include: a voltage of 60 to 90 kV, specifically 60, 70, 80 or 90 kV, and an electrostatic current of 10 to 20 μA, specifically 10, 15 or 20 μA.

[0076] In the present invention, the curing temperature is preferably 160-180° C., specifically 160, 170 or 180° C., and the curing time is preferably 10-40 min, specifically 10, 20, 30 or 40 min.

[0077] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0078] Example 1

[0079] The raw materials for preparing acrylic resin include the following components by mass: 10 parts of soft monomer butyl acrylate, 40 parts of hard monomer methyl methacrylate, 10 parts of styrene, 35 parts of first crosslinking monomer glycidyl methacrylate, 0.2 parts of second crosslinking monomer allyl methacrylate, 1 part of initiator tert-butyl hydroperoxide and 120 parts of solvent xylene. The preparation process includes the following steps:

[0080] According to the formula, the soft monomer, the hard monomer, the first cross-linking monomer, the second cross-linking monomer and the initiator are uniformly mixed to fully dissolve the initiator to obtain a mixed solution; the solvent is added to a reactor equipped with heating, stirring, condensation and reflux, and nitrogen is passed through for 30 minutes, and then the temperature is raised to 138°C (the heating table temperature is set at 80°C, and the temperature is raised by 20°C every 15 minutes) with stirring. After the temperature is constant, the mixed solution is added dropwise at a uniform speed, and the addition is completed within 3 hours. The mixture is kept warm for 2 hours, and then, the solvent is evaporated by reduced pressure distillation at a vacuum degree of 0.098 MPa and a temperature of 100°C until there is basically no fraction evaporated, thereby obtaining the acrylic resin.

[0081] Example 2

[0082] The same as Example 1, the only difference is that the raw materials include the following components in parts by mass: 10 parts of soft monomer butyl acrylate, 70 parts of hard monomer methyl methacrylate, 50 parts of first cross-linking monomer glycidyl methacrylate, 0.5 parts of second cross-linking monomer allyl methacrylate, 5 parts of initiator tert-butyl hydroperoxide and 300 parts of solvent xylene.

[0083] Example 3

[0084] The same as Example 1, the only difference is that the raw materials include the following components in parts by mass: 60 parts of soft monomer butyl acrylate, 70 parts of hard monomer methyl methacrylate, 50 parts of first cross-linking monomer glycidyl methacrylate, 0.5 parts of second cross-linking monomer allyl methacrylate, 5 parts of initiator tert-butyl hydroperoxide and 300 parts of solvent xylene.

[0085] Example 4

[0086] The same as Example 1, the only difference is that the raw materials include the following components in parts by mass: 60 parts of soft monomer butyl acrylate, 30 parts of hard monomer methyl methacrylate, 20 parts of first cross-linking monomer glycidyl methacrylate, 0.5 parts of second cross-linking monomer allyl methacrylate, 1 part of initiator tert-butyl hydroperoxide and 60 parts of solvent xylene.

[0087] Example 5

[0088] The same as Example 1, the only difference is that the raw materials include the following components in parts by mass: 10 parts of soft monomer butyl acrylate, 40 parts of hard monomer methyl methacrylate, 40 parts of first cross-linking monomer glycidyl methacrylate, 0.4 parts of second cross-linking monomer allyl methacrylate, 5 parts of initiator tert-butyl hydroperoxide and 90.4 parts of solvent xylene.

[0089] Example 6

[0090] The same as Example 1, the only difference is that the mixed solution is added dropwise within 4 hours.

[0091] Example 7

[0092] The same as Example 1, the only difference is that the mixed solution is added dropwise within 5 hours.

[0093] Example 8

[0094] The same as Example 1, the only difference is that the mixed solution is added dropwise within 6 hours.

[0095] Example 9

[0096] The same as Example 1, the only difference is that after stirring and heating to 130°C (the temperature of the heating table is set at 80°C, and the temperature rises by 20°C every 15 minutes) and becomes constant, the mixed solution is added dropwise at a uniform speed to carry out polymerization reaction.

[0097] Example 10

[0098] The same as Example 1, the only difference is that stirring is started, the temperature is raised to 150°C (the temperature of the heating table is set at 80°C, and the temperature rises by 20°C every 15 minutes), and then the mixed solution is added dropwise at a uniform speed to carry out polymerization reaction.

[0099] Embodiment 11

[0100] The same as Example 1, the only difference is that the second cross-linking monomer allyl methacrylate is replaced by allyl acrylate.

[0101] Comparative Example 1

[0102] The same as Example 1, the only difference is that the second cross-linking monomer allyl methacrylate is replaced by glycidyl methacrylate.

[0103] The epoxy value, number average molecular weight and molecular weight distribution of the acrylic resins prepared in the examples and comparative examples were tested, and the results are shown in Table 1.

[0104] Application Examples

[0105] 100 parts by mass of the acrylic resin prepared in the embodiment and the comparative example, 40 parts by mass of the solid agent undecane dioic acid and 2 parts by mass of the accelerator 2-methylimidazole were mixed uniformly at 120° C., and then crushed, ground and passed through a 120-mesh sieve to obtain an acrylic powder coating. The acrylic powder coating was sprayed onto an aluminum plate wiped with ethanol using an electrostatic spraying technology with an electrostatic spraying voltage of 60 kV and an electrostatic current of 10 μA, and then cured at 180° C. for 10 min to obtain a paint film.

[0106] Performance Testing

[0107] (1) Appearance: Visually inspect whether the surface of the paint film obtained after curing is smooth;

[0108] (2) Light transmittance: tested according to the method specified in GB / T 40415-2021;

[0109] (2) Flexibility: Tested according to the method specified in GB / T 1731-1993;

[0110] (3) Impact resistance: tested according to the method specified in GB / T 1732-1993;

[0111] (4) Weather resistance: tested according to the method specified in GB 1767-79 (89);

[0112] (5) Thermal stability test: The test was conducted in accordance with the method for determination of shrinkage of plastic thermosetting molding materials in GB / T 39818-2021. The test conditions were 150°C and 30 min.

[0113] The test results are shown in Table 1. As can be seen from Table 1, the acrylic resin prepared in Example 5 has the best performance and the best thermal stability.

[0114] Table 1 Performance test results

[0115]

[0116] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. An acrylic resin, characterized in that It is prepared from the following raw materials in parts by weight: 10-60 parts of soft monomer, 30-70 parts of hard monomer, 20-50 parts of first crosslinking monomer, 0.2-0.5 parts of second crosslinking monomer, 1-5 parts of initiator and 60-300 parts of solvent; The first crosslinking monomer contains an epoxy group; the second crosslinking monomer contains at least two unsaturated bonds, and the at least two unsaturated bonds include a terminal carbon-carbon double bond; The soft monomer is an alkyl acrylate compound.

2. The acrylic resin according to claim 1, characterized in that The second crosslinking monomer includes allyl methacrylate and / or allyl acrylate.

3. The acrylic resin according to claim 1 or 2, characterized in that The mass fraction of the second cross-linking monomer in the raw material is 0.3 to 0.4 parts.

4. The acrylic resin according to claim 1, characterized in that The first cross-linking monomer includes one or more of glycidyl methacrylate, glycidyl acrylate, 4-hydroxybutyl acrylate glycidyl ether and versatile glycidyl carbonate.

5. The method for preparing an acrylic resin according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing the soft monomer, the hard monomer, the first crosslinking monomer, the second crosslinking monomer and the initiator to obtain a mixed solution; The mixed solution is added dropwise into a solvent to carry out a polymerization reaction, thereby obtaining the acrylic resin.

6. The preparation method according to claim 5, characterized in that: The dropping time is 3 to 6 hours.

7. The preparation method according to claim 5, characterized in that: The temperature of the solvent is 130-150°C.

8. The preparation method according to claim 5, characterized in that: The polymerization reaction temperature is 130-150° C., and the insulation time is 1-4 hours, wherein the insulation time is calculated from the completion of the dropwise addition.

9. Use of the acrylic resin according to any one of claims 1 to 4 or the acrylic resin prepared by the preparation method according to any one of claims 5 to 8 as a photovoltaic module encapsulation material.

10. An acrylic powder coating, characterized in that: The invention comprises the following components in parts by mass: 100-140 parts of resin, 12-40 parts of curing agent and 0.2-2 parts of accelerator, wherein the resin is the acrylic resin according to any one of claims 1 to 4 or the acrylic resin prepared by the preparation method according to any one of claims 5 to 8.

Citation Information

Patent Citations

  • Waterborne acrylic acid body matting resin and preparation method thereof

    CN110172121A

  • Liquid methacrylic acid functionalized POSS, photo-cured acrylic resin modified by liquid methacrylic acid functionalized POSS, and preparation methods thereof

    CN111116915A

  • Water-based acrylic emulsion as well as preparation method and application thereof

    CN111944103A

  • Epoxy acrylic powder coating resin and preparation method and application thereof

    CN115651473A

  • High-light-transmittance acrylic acid powder resin and preparation method thereof

    CN117701092A